Effects of neck-specific exercise with or without a behavioural approach in addition to prescribed physical activity for individuals with chronic whiplash-associated disorders: a prospective randomised study - Peolsson, Anneli (BMC Musculoskelet Disord, 2013)
BACKGROUND: Up to 50% of chronic whiplash associated disorders (WAD) patients experience considerable pain and disability and remain on sick-leave. No evidence supports the use of physiotherapy treatment of chronic WAD, although exercise is recommended. Previous randomised controlled studies did not evaluate the value of adding a behavioural therapy intervention to neck-specific exercises, nor did they compare these treatments to prescription of general physical activity. Few exercise studies focus on patients with chronic WAD, and few have looked at patients’ ability to return to work and the cost-effectiveness of treatments. Thus, there is a great need to develop successful evidence-based rehabilitation models. The study aim is to investigate whether neck-specific exercise with or without a behavioural approach (facilitated by a single caregiver per patient) improves functioning compared to prescription of general physical activity for individuals with chronic WAD. METHODS/DESIGN: The study is a prospective, randomised, controlled, multi-centre study with a 2-year follow-up that includes 216 patients with chronic WAD (> 6 months and < 3 years). The patients (aged 18 to 63) must be classified as WAD grade 2 or 3. Eligibility will be determined with a questionnaire, telephone interview and clinical examination. The participants will be randomised into one of three treatments: (A) neck-specific exercise followed by prescription of physical activity; (B) neck-specific exercise with a behavioural approach followed by prescription of physical activity; or (C) prescription of physical activity alone without neck-specific exercises. Treatments will be performed for 3 months. We will examine physical and psychological function, pain intensity, health care consumption, the ability to resume work and economic health benefits. An independent, blinded investigator will perform the measurements at baseline and 3, 6, 12 and 24 months after inclusion. The main study outcome will be improvement in neck-specific disability as measured with the Neck Disability Index. All treatments will be recorded in treatment diaries and medical records. DISCUSSION: The study findings will help improve the treatment of patients with chronic WAD. TRIALS REGISTRATION: ClinicalTrials.gov identifier: NCT01528579.